An Assessment of the Sasakawa Africa Fund for Extension Education’s (SAFE) Training Program in Mali: Graduates’ Perceptions of the Program’s Impact on Their Professional Performance - Assa Kanté; Craig M Edwards; Cindy Blackwell (Journal of International Agricultural and Extension Education, 2013)
The Sasakawa Africa Fund for Extension Education (SAFE) was established in nine African countries to overcome a shortage of qualified extension educators. A study was commissioned on the SAFE program in Mali, where it has operated since 2002. The purpose of this study was to assess SAFE graduates’ perceptions regarding their training experiences and its impact on their professional practices. Human capital, experiential learning, social constructivism, and selfefficacy theories supported interpreting the SAFE graduates’ perceptions of the competencies acquired and the changes they perceived making to their clients’ practices. A purposeful sampling approach was used to survey 50 SAFE graduates. The graduates’ responses were gathered using several types of response scales, including Likert-type. The findings revealed that 80% of the respondents were males in their late forties with an average of 17 years of experience in extension. On entering the SAFE training program, 70% held a Technician degree; 30% held a Diplôme Universitaire de Technicien Supérieur (DUTS; Higher Technician Degree); and seven in ten had majored in agriculture. The SAFE graduates perceived, as outcomes of their training, improvements in their professional competence, in their job category, and in their clients’ practices. Moreover, graduates perceived they delivered more “extension services” through demonstrations and discussions with male and female clients after their training, but a smaller increase in interactions with dealers and traders was reported. The researchers recommended increasing female participation in the SAFE training program, focusing more on value-chain-oriented curricula, and conducting an assessment of clients’ perceptions of the SAFE-trained extension educators’ impact on their practices.
Keywords: Assessment; Extension; Human capital; Mali; Self-efficacy; Training